The role of education in promoting interreligious coexistence - Al-Herbawi, Fatima Fayez (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to define the concept and goals of coexistence between religions, and to clarify the most important factors affecting the achievement of coexistence between religions, and define the role Education in promoting the values ​​of coexistence between religions. And offer some proposals to enhance the role of education in promoting the values ​​of coexistence between religions. The results indicated that education has a major role in promoting the values ​​of inter-religious coexistence among members of society. And that coexistence between religions has become necessary today. And that the teacher plays a great role in consolidating the values ​​of coexistence and acceptance of others who differ with us in thought or belief. And that coexistence between people is a universal year that God Almighty wanted for His servants of different colors, religions, thoughts, and beliefs.